Changes in Relationship‐Specific Attachment in Emotionally Focused Couple Therapy. (29th October 2015) - Burgess Moser, Melissa; Johnson, Susan M.; Dalgleish, Tracy L.; Lafontaine, Marie‐France; Wiebe, Stephanie A.; Tasca, Giorgio A.
Abstract : Emotionally focused couple therapy (EFT; Johnson, The practice of emotionally focused couple therapy (1st/2nd edition). Brunner‐Routledge, New York, 2004) is an effective treatment of relationship distress (Johnson et al., Clinical Psychology: Science and Practice, 1999; 6, 67). However, less is known about EFT's impact on couples' relationship‐specific attachment bond. Using hierarchical linear modeling with a sample of 32 couples, we examined session‐by‐session changes in couples' relationship‐specific attachment anxiety and avoidance and pre‐ to posttherapy changes in their relationship‐specific attachment behaviors. Couples significantly decreased in relationship‐specific attachment avoidance, and those who completed a blamer softening significantly decreased in relationship‐specific attachment anxiety. Couples' attachment behavior significantly increased toward security. Finally, session‐by‐session decreases in relationship‐specific attachment anxiety and avoidance were significant associated with increases in relationship satisfaction across sessions. These results provide empirical support for the attachment‐based assumptions of EFT. Video abstract accessible by clicking here Abstract : Video abstract accessible by clicking here